Population-level effects of clam harvesting on the seagrass Zostera noltii - Cabaço, Susana (2018)
Seagrass declines have been reported worldwide, mostly as a consequence of anthropogenic disturbance. In Ria Formosa lagoon, southern Portugal, the intertidal meadows of Zostera noltii are highly disturbed by clam harvesters. The most common technique used to collect the clams consists of digging and tilling the sediment with a modified knife with a large blade. Here we present both descriptive and experimental evidence of the negative effects of clam harvest on the Z. noltii populations of Ria Formosa. A comparison between disturbed and undisturbed meadows suggests that clam harvesting activities change the species population structure by significantly reducing shoot density and total biomass, particularly during August, when the harvest effort is higher. Experimental harvest revealed a short-term impact on shoot density, which rapidly recovered to control levels during the following month. An experimental manipulation of rhizome fragmentation revealed that plant survival is reduced only when fragmented rhizomes are left with 1 intact internode. Shoot production and rhizome elongation and production of fragmented rhizomes having 2 to 5 internodes were not significantly affected, even though growth and production were lower when only 2 internodes were left. Experimental shoot damage at different positions along the rhizome had a significant effect on plant survival, rhizome elongation, and production only when the apical shoot was removed. Our results show that clam harvest can adversely affect Z. noltii meadows of Ria Formosa while revealing a low modular integration that allows the species to rapidly recover from physical damage.